2022
DOI: 10.1186/s40168-022-01376-y
|View full text |Cite
|
Sign up to set email alerts
|

Functional differentiation determines the molecular basis of the symbiotic lifestyle of Ca. Nanohaloarchaeota

Abstract: Background Candidatus Nanohaloarchaeota, an archaeal phylum within the DPANN superphylum, is characterized by limited metabolic capabilities and limited phylogenetic diversity and until recently has been considered to exclusively inhabit hypersaline environments due to an obligate association with Halobacteria. Aside from hypersaline environments, Ca. Nanohaloarchaeota can also have been discovered from deep-subsurface marine sediments. Results Thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 77 publications
1
10
0
Order By: Relevance
“…[15,[78][79][80][81][82][83]. Within putatively novel phyla, a higher diversity of Patescibacteria and Nanoarchaeota has been observed in hypersaline lake environments compared to other environments, aligning with previous findings of saline lake studies [15,24]. Some MAGs, such as Caldatribacteriota and KSB1, were rarely reported in other environments except marine sediments [84,85] or, as is the case of Margulisbacteria in underground water environments [86].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…[15,[78][79][80][81][82][83]. Within putatively novel phyla, a higher diversity of Patescibacteria and Nanoarchaeota has been observed in hypersaline lake environments compared to other environments, aligning with previous findings of saline lake studies [15,24]. Some MAGs, such as Caldatribacteriota and KSB1, were rarely reported in other environments except marine sediments [84,85] or, as is the case of Margulisbacteria in underground water environments [86].…”
Section: Discussionsupporting
confidence: 83%
“…3d). These archaea have been considered as symbionts, exhibiting intracellular lifestyles with other prokaryotic cells [24, 64]. Several putatively novel phyla were exclusively identified in ADH and BLK sediments (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, two of the received MAGs belong to the Nanosalinaceae family which is a part of the phylum Nanohaloarchaeota, which is part of DPANN superphylum. This taxon includes non-cultured microorganisms living in symbiosis with Halobacteria, characterized by small genomes and limited metabolic capabilities (Castelle et al 2018 ; Xie et al 2022 ). Due to the still incomplete characterization of microorganisms belonging to the Nanohaloarchaeota, the obtained MAGs may bring significant value to further research.…”
Section: Discussionmentioning
confidence: 99%
“…Both the binned genomes showed that they have genes associated with DNA replication, DNA repair, transcription, and translation but lack the biosynthetic capacity to synthesize nucleotides, a few amino acids, lipids, and other cofactors. The absence of such essential biosynthetic pathways implies that they may likely have a symbiotic lifestyle (Xie et al, 2022). The binned genomes also showed the presence of partial tricarboxylic acid (TCA) cycle and capability of the archaea in having anaerobic metabolism.…”
Section: Discussionmentioning
confidence: 99%